Antiviral, Antibacterial, Antifungal, and Anticancer Activity of Plant Materials Derived from Cymbopogon citratus (DC.) Stapf Species - Anna Kiełtyka-Dadasiewicz; Javier Esteban; Agata Jabłońska-Trypuć (MDPI AG, 2024)
The importance of natural plant materials in modern medicine is considerable, and raw materials with antiviral, antibacterial, antifungal, and anticancer properties are still sought because of microbe resistance and difficulties in anticancer therapy. This review focuses on the lemongrass Cymbopogon citratus (DC.) Stapf. and on the lemongrass oil properties and applications. Multiple applications of this plant were described in different latitudes and cultures, including cases of digestive disorders and anti-inflammatory, antipyretic, diaphoretic, stimulating, and antispasmodic conditions. Data from the literature on the composition of essential oil and extracts from C. citratus were analyzed, and the results of research on the antifungal, antibacterial, and antiviral effects were quoted. Essential oil inhibits the growth of fungi (Aspergillus niger, A. fumigatus, Candida spp.) and has an antibacterial effect (Staphylococcus aureus, Bacillus subtilis, Pseudomonas aeruginosa). It also shows antiviral activity and deters insects. Lemongrass contains active substances with potential anticancer effects. This plant has apoptosis-stimulating properties, mainly through the activity of apigenin, which is the main active flavonoid in this plant. This active substance helps inhibit cell proliferation by stopping the cell cycle and directing cancer cells toward apoptosis.